Meta-Analysis: Trends of Digital Democracy Research Publications - Ali, Muhammad; Jailani, Muhammad Aprian; Setiawan, Rendi Eko Budi; Kurniawan, Cahyadi (Journal of Government and Civil Society, 2023)
Digital democracy has become a contemporary study in social and political science, but theoretically the term digital democracy does not yet have a definite pattern, this makes digital democracy fail to be understood both theoretically and practically. Therefore, this research has basic questions about; how the theoretical development of digital democracy through the trend of research publications based on the Scopus index. This article uses a qualitative description methodology, and data analysis techniques using research software; Vosviewer and NVivo 12 plus. The findings in this study see that scholars focus on the theme of e-government and digital political participation, in e-government the research theme focuses on government services through open government data and studies on the function of official government social media for public communication. While the research theme of digital political participation focuses on the study of e-voting and digital social movement. Digital democracy in a positive perspective can also encourage the character of a deliberative democratic system. Referring to the data of research publications that have been analyzed, the researcher concludes a new finding: that digital democracy can theoretically be categorized into two. First, the electoral aspect, which understands that digital democracy creates a digital transformation of government work, which is marked by open government data, digital services, and digital information. Second, the-non electoral aspect, which sees digital democracy as an opportunity for civil society to be involved in political participation in a country, such as electronic elections, online political participation, and digital activism. Demokrasi digital menjadi suatu kajian yang kontemporer dalam ilmu sosial dan politik, namun secara teoritis term demokrassi digital belum mempunyai pola yang pasti, hal ini menjadikan demokrasi digital gagal dipahami baik secara teoritis maupun praktis. Karena itu penelitian ini mempunyai pertanyaan dasar tentang; bagaimana perkembangan teoritis demokrasi digital melalui trend publikasi penelitian berbasis indeks scopus. Artikel ini menggunakan metodologi deskripsi kualitatif, dan teknik analisis data menggunakan software penelitian; Vosviewer dan NVivo 12 plus. Temuan dalam penelitian ini melihat para sarjana fokus pada tema e-government dan partisipasi politik secara digital, dalam e-government tema penelitian fokus kepada pelayanan pemerintah melalui open data government dan kajian fungsi media sosial resmi pemerintah untuk komunikasi publik. Sedangkan tema penelitian partisipasi politik digital fokus pada kajian e-voting dan digital sosial movement. Demokrasi digital dalam perspektif positif juga dapat mendorong karakter sistem demokrasi yang deliberatif. Merujuk data publikasi penelitian yang telah dianalisis, peneliti menyimpulkan temuan baru: bahwa demokrasi digital secara teoritis dapat dikategorikan menjadi dua. Pertama, aspek elektoral yang memahami bahwa demokrasi digital membuat transformasi kerja pemerintahan secara digital, yang ditandai dengan open data government, pelayanan digital, dan informasi digital. Kedua, aspek non elektoral, yang melihat demokrasi digital menjadi peluang untuk masyarakat sipil terlibat dalam partisipasi politik dalam suatu negara, seperti pemilu elektronik, partisipasi politik onlline, dan aktivisme digital.